Effect of frequency on droplet actuation in reverse electrowetting. (1st March 2023) - Wang, Li-Ming; Zhao, Rui; Liang, Zhong-Cheng; Zhang, Jian; Kou, Song-Feng
Abstract: In this work, a theoretical formula based on equivalent circuit model is proposed to describe the influence of frequency on the droplet actuation behavior in reverse electrowetting. To verify the theory, changes of droplet profile are monitored by charge coupled device (CCD) camera and simulated by COMSOL. It shows that the threshold voltage required for the droplet to start contracting inward increases firstly and then decreases with the increasing frequency. When the frequency is 1 kHz, the threshold voltage reaches the maximum value. Once the droplet begins to move inward, its contact angle increases with the working voltage. As for 4 kHz, the contact angle increases linearly from 60° to 154° when voltage ranges from 16 V to 50 V, while the droplet remained stationary when U < 16 V. The relative experimental results well accord with the theoretical prediction.